Experimental Study of Lithium-ion Battery Performance Based on Mini-channel Cooling Plate - Ihsan Pratama Rushadiawan; Dominicus Danardono Dwi Prija Tjahjana; Muhammad Nizam; Julian Fikri Arifwardana; Mufti Reza Aulia Putra (Universitas Sebelas Maret (UNS), 2024)
Making efficient batteries is important nowadays. One potential problem that can hinder this is the thermal runaway that occurs in battery cells. There are various causes of thermal runaway, one of the most common is an increase in temperature that exceeds the optimal allowable limit. Additional cooling will be required in vehicles that use batteries. Battery Thermal Management System (BTMS) with mini-channel cooling plate is one of the methods often used to maintain battery performance. In this study, the performance of Lithium-ion batteries is affected by fluid flow velocity. The experimental process was carried out by charging and discharging with a C-rate of 1C. Cooling is done with ethylene glycol fluid with fluid velocity variations of 0.21 L/min; 0.42 L/min and 0.63 L/min. The results show that fluid flow velocity affects the final battery temperature and battery performance. The optimal fluid velocity is shown at 4.2 L/min. At this speed it can reduce the battery temperature by 6.7°C.